(untitled) (Scientific journal of the Fergana State University, 2023)
Nowadays the humankind deals with the complex open systems, regarding the society and the changes taking place in it belong to a complex system. A complex system consists of complex elements. Complex systems are researched by synergetic ideas, terms and methods. In the given article, problems, such as, a term of system, and its meaning, its differences from the object used in the classical science, becoming wholeness by inter-influence of elements and inter-connection of them are philosophically analysed